Microtus gregalis - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus gregalis (Pallas, 1779). Nova Spec. Quad. Glir. Ord., p. 238. TYPE LOCALITY: Siberia, E of Chulym River. DISTRIBUTION: Palearctic tundra of Siberia from White Sea to far northeast, and wooded steppe from S Urals east to Amur and NE China (Heilongjiang), south to Aral Sea, Pamirs, Tien Shan and Altai Mtns, N Mongolia, and NW China (Xinjiang) (see Corbet, 1978c; Rausch, 1964). SYNONYMS: angustus, brevicauda, buturlini, castaneus, dolguschini, dukelskiae, eversmanni, kossogolicus, major, montosus, nordenskioldi, pallasii, raddei, ravidulus, sirtalaensis, slowzovi, talassicus, tarbagataicus, tianschanicus, tundrae, unguiculatus, zachvatkini. COMMENTS: Subgenus Stenocranius. The only Asian species in the subgenus (Zagorodnyuk, 1990). Intraspecific variation in chromosomal traits among Mongolian samples documented by Kovalskaya (1989) and earlier chromosomal data summarized and reviewed by Zima and Krâl (1984a). Based on morphological and zoogeographic criteria, Rausch (1964) considered the North American miurus to be conspecific with Asian gregalis, a connection refuted by Fedyk (1970) with chromosomal data and by Vorontsov and Lyapunova (1986). Zagorodnyuk (1990) emphasized the karyotypic divergence between gregalis and miurus by listing the latter in the M. middendorffi species group along with M. mongolicus and M. sachalinensis, subgenus Alexandromys. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 521, DOI: 10.5281/zenodo.7353098